PENGARUH INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN KIMIA YANG TERDAFTAR DI BEI TAHUN 2017-2021 - Rizky Pramudya; Nugroho Mardi Wibowo; Hadi Susanto (Universitas Sains dan Teknologi Komputer, 2022)
The purpose of this study is to determine the condition of intellectual capital, financial performance and firm value, to analyze and prove financial performance can be influenced by intellectual capital, to analyze and prove firm value can be influenced by intellectual capital, to analyze and prove firm value can be influenced by performance. finance, analyze and prove the value of the company can be influenced by intellectual capital through the financial performance of a chemical company. associative research is research that is causal (explains the relationship between two or more variables) and a causal relationship, there are independent and dependent variables. The population of chemical sector companies listed on the Indonesia Stock Exchange in 2017-2021, totaling 14 companies. The data used is secondary data sourced from financial statement data of chemical sector companies listed on the Indonesia Stock Exchange in 2017-2021. The data analysis technique used in this study uses path analysis which is then processed using Partial Least Square (PLS). Firm value is an investor's perception of the company's level of success which is often associated with stock prices and profitability. High stock prices make the value of the company also high. A high company value will make the market believe not only in the company's current performance, but also in the company's prospects in the future